The engagement of Civil Society Organizations in Brazilian South-South Cooperation: towards a comprehensive approach to participation - Dolcetti-Marcolini, Michele (Iberoamerican Journal of Development Studies, 2014)
Dynamics of South-South (SSC) and Triangular Cooperation provided challenging interpretations and gained an autonomous space in the agendas of development and international cooperation’s research. Recently, we observed the emergence of critical contributions from civil society, trying to impact the development cooperation of southern countries. Civil Society Organizations (CSOs) suggest alternative principles and practices, re-appropriating their interpretations about participation, which were traditionally elaborated from northern CSOs. Nowadays, there are no structured studies describing these dynamics. This article, through the experience of civil society articulations in Brazilian SSC, tries to propitiate this research, encouraging the formulation of alternative action frames and the rise of interpretations from the South. To do so, we analyze how Brazilian CSOs try to enhance their role in formulation, implementation and accountability of Brazilian SSC, with their articulation in domestic spaces of participation and through autonomous cooperation actions.